Computed Tomography Angiography of the Aorta—Optimization of Automatic Tube Voltage Selection Settings to Reduce Radiation Dose or Contrast Medium in a Prospective Randomized Trial. Issue 5 (May 2021) - Euler, André; Taslimi, Tilo; Eberhard, Matthias; Kobe, Adrian; Reeve, Kelly; Zimmermann, Alexander; Krauss, Andreas; Gutjahr, Ralf; Schmidt, Bernhard; Alkadhi, Hatem
Abstract : Objectives: The aim of this study was to compare the image quality of low-kV protocols with optimized automatic tube voltage selection (ATVS) settings to reduce either radiation dose or contrast medium (CM) with that of a reference protocol for computed tomography angiography (CTA) of the thoracoabdominal aorta. Materials and Methods: In this institutional review board–approved, single-center, prospective randomized controlled trial, 126 patients receiving CTA of the aorta were allocated to one of three computed tomography protocols: (A) reference protocol at 120 kVp and standard weight-adapted CM dose; (B) protocol at 90 kVp, reduced radiation and standard CM dose; and (C) protocol at 90 kVp, standard radiation and reduced CM dose. All three protocols were performed on a third-generation dual-source computed tomography scanner using the semimode of the ATVS system. The image-task-dependent optimization settings of the ATVS (slider level) were adjusted to level 11 (high-contrast task) for protocols A and B and level 3 (low-contrast task) for protocol C. Radiation dose parameters were assessed. The contrast-to-noise ratios (CNRs) of protocols B and C were tested for noninferiority compared with A. Subjective image quality was assessed using a 5-point Likert scale. Results: Size-specific dose estimate was 34.3% lower for protocol B compared with A ( P < 0.0001). Contrast medium was 20.2% lower for protocol C compared with A ( P < 0.0001). Mean CNR in B and C was noninferior to protocol A (CNR of 30.2 ± 7, 33.4 ± 6.7, and 30.5 ± 8.9 for protocols A, B, and C, respectively). There was no significant difference in overall subjective image quality among protocols (4.09 ± 0.21, 4.03 ± 0.19, and 4.08 ± 0.17 for protocols A, B, and C, respectively; P = 0.4). Conclusions: The slider settings of an ATVS system can be adjusted to optimize either radiation dose or CM at noninferior image quality in low-kV CTA of the aorta. This optimization could be used to extend future ATVS algorithms to take clinical risk factors like kidney function of individual patients into account.